(untitled) (Indonesian Court and Justice Review, 2024)
Environmental disputes in Indonesia often involve complex issues related to land use, natural resource management, and environmental degradation, with significant consequences for both public health and biodiversity. The Administrative Court, as a specialized judicial body, plays a central role in resolving such disputes, yet its effectiveness in delivering justice remains a topic of debate. This study evaluates the performance of the Administrative Court in handling environmental cases, focusing on the court’s ability to ensure fair and timely resolution, protect environmental rights, and hold government entities accountable for their actions. Using a mixed-methods approach, the research combines an analysis of case law, court rulings, and interviews with legal professionals, environmental activists, and affected stakeholders to assess the strengths and weaknesses of the Administrative Court in addressing environmental disputes. The findings indicate that while the court has made significant contributions to environmental justice, challenges such as inconsistent rulings, limited legal resources, and the lack of specialized environmental expertise hinder its full potential. Moreover, the relationship between government agencies and the judiciary often leads to tensions that affect the court’s independence and its ability to deliver impartial rulings. The novelty of this study lies in its in-depth examination of the Administrative Court’s performance in the context of environmental disputes, offering both critical insights and practical recommendations for improving its effectiveness. As environmental issues become increasingly urgent, this research contributes to the ongoing dialogue on judicial reform and the role of the judiciary in promoting sustainable development and environmental protection in Indonesia.